A new species of the genus Fernandezina Birabén, 1951 (Araneae: Palpimanidae: Otiothopinae) from Colombia - Martínez, Leonel; Gutierrez, Luis Carlos (Zootaxa, 2021)
Specimens of the palpimanid spider subfamily Otiothopinae Platnick are commonly collected in soil and leaf litter in tropical and subtropical environments (Platnick 1975; Cala-Riquelme et al. 2018). However, otiothopines are generally poorly represented in biological collections and usually collected in low numbers during field campaigns, with many species represented by only a single sex (Cala-Riquelme et al. 2018). These difficulties, combined with our scarce knowledge of the biology and natural history of these spiders, mean that there are regional gaps in our systematic understanding of the group. Thus, taxonomic additions and notes about natural history are essential in order to increase our knowledge of the group and gradually close those gaps.